Pengaruh Ketebalan Briket Arang terhadap Perubahan Temperatur dan Kelembaban pada Desalinasi Surya Sistem Interfacial Heating - Siagian, Saut Ronny Tuah; Jafri, Muhamad; Tarigan, Ben V.; Riwu, Defmit B. N.; Adoe, Dominggus G. H. (Universitas Nusa Cendana, 2022)
Solar desalination is the process of reducing brine salinity by using heat from the sun to produce fresh water. Distillation is one of the traditional solar desalination methods, but it has a low evaporation rate. Recently, interfacial solar evaporation by thermal localization at the liquid interface has been proposed as a promising alternative to evaporation. In this study, briquettes were investigated as as the interface solar absorber to increase vapor production. Experiments were carried out in 4 single-slope type distillers for 8 hours under clear sunlight using 10, 15 and 20 mm thick briquettes. For comparison, we also looked at distiller (basin) with no charcoal. Temperatures and humidity were measured at several position within the basin to identify factors contributing to seawater evaporation. We found that the vapor production increases when temperature is high and humidity is low. While condensation is highly dependent on humidity, high humidity is able to make water vapor molecule reach its dew point faster. This condensation process will greatly impact the productivity of the distillate.